Elucidating the mechanism of wheat bran arabinoxylan on the freeze-thaw stability of gluten protein: From the perspectives of spatial conformation and molecular polymerization of gluten protein and micro-morphology of gluten network - Mengyuan Li; Lingfang Zhang; Yuwen Wang; Xichen Lin; Xinhao Li; Li Li; Sen Ma (Food Hydrocolloids, 2026)

Synergistic effects of biochar and probiotic fermentation agent on soil aggregate stability, carbon sequestration, and heavy metal(loid)s passivation in paddy fields - Keqi Zhao; Xue Yu; Xifeng Qin; Ruijie Li; Lin Luo; Xiaomei Yang; Liuqin He; Anwei Chen; Jiachao Zhang; Hongli Huang; Xichen Zhao (Agriculture, Ecosystems & Environment, 2026)

Drought destabilizes diatom co-occurrence network in a tropical shallow Lake - Yingzhi Jia; Xumei Lai; Xichen Quan; Yingying Fei; Mengna Liao; Kai Li; Xiao Zhang; Jian Ni (Quaternary Science Reviews, 2026)

Evaluating AMIP6 Models of the Indian Ocean–North America Teleconnection Associated with the Indian Ocean Basin Mode - Duan Zhang; Yurong Hou; Xichen Li (Advances in Atmospheric Sciences, 2026)

Wettability-switchable deep bed filtration for efficient oily wastewater treatment - Song Xichen; Yan Yaping; Zhang Tingting; Zhou Jianqiang; Wang Xiaojuan; Wang Zhezhe; Lin Jialong; Wang Ting; Song Xiaosan; Dai Liang; Wang Gang; Gao Suxia; et al. (Journal of Hazardous Materials, 2026)

Dredging changes the controls, pathways and environmental sensitivity of N2O emissions in shallow lakes - Rongwei Xiong; Yong Li; Ming Chen; Zhiyang Zhou; Zhengliang Jiang; Xichen Che (Journal of Environmental Management, 2026)

Consistency and specificity of soil and microbial responses among crops to mulching practices in semi-arid rainfed agroecosystems in China - Yao Zhang; Yuwei Chai; Xichen Wang; Hongbo Cheng; Yawei Li; Jiantao Ma; Lei Chang; Shouxi Chai (European Journal of Agronomy, 2026)

Effect of regional Hadley circulation–subtropical jet interaction: enhancement of the Central-Pacific ENSO teleconnection in the Southern Hemisphere - Weihan Ma; Juan Feng; Yujie Miao; Weiqi Wang; Xichen Li (Climate Dynamics, 2026)

Tropical oceans drive decadal trends in surface mass balance over Wilkes Land, East Antarctica - Kai Man; Xichen Li; Yetang Wang; Guitao Shi; Lei Geng; Yonghao Wang; Yujie Miao; Weihan Ma (Climate Dynamics, 2026)

Preseason ENSO signals and the underlying mechanisms driving soybean yield anomaly in the Americas - Menghan Li; Xichen Li (European Journal of Agronomy, 2026)

Efficient pollutant removal by iron-carbon bioretention system in long-term operation: Stability and performance - Zhou Jianqiang; Song Xichen; Wang Xiaojuan; He Jiangtao; Zhou Yawen; Qin Jie; Xiao Yifei; Gao Suxia; Li Hua; Liu Jianlin; Li Wei; Cao Lianbao; et al. (Journal of Environmental Chemical Engineering, 2026)

Removal performance and mechanisms of microplastics by superhydrophobic medium - Zhang Tingting; Cheng Wenqing; Wang Xiaojuan; Yan Yaping; Song Xichen; Zhou Jianqiang; Liu Xiuyun; Gao Suxia; Li Hao; Liu Jianlin; Cao Lianbao; Li Wei; et al. (Journal of Environmental Chemical Engineering, 2026)

Magnetic chronology of the late Miocene Wulangou red clay sequences in the northern Otindag Sandy Land - Hongyu Qi; Yali Zhou; Jiangli Pang; Xiaoke Qiang; Jiale Wang; Baofeng Ma; Tong Feng; Xichen Li; Yiting Zhao; Yingying Cui; Liping Jiang; Siying Yue (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

2-Hydroxyanthraquinone exposure causes the damage of cerebrovascular and blood brain barrier in zebrafish via inducing inflammation and downregulation of the Wnt/β-catenin signaling pathway - Huimin Li; Ziang Wang; Suwei He; Minghui Zhong; Xichen Wang; Weitao Hu; Jingrong Tang; Zhonghao Xiao; Xiaowen Shi; Zigang Cao (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

From waiting to moving: how golden snub-nosed monkeys facilitate a group departure - Wei Li; Xichen Zhang; Yuhang Li; Tong Wu; Xiaowei Wang; Chengliang Wang; Ruliang Pan; Baoguo Li (Behavioral Ecology and Sociobiology, 2026)

Metyrapone supplementation mitigates cortisol-mediated growth inhibition and sex bias in high-density cultured Japanese eels Anguilla japonica - Bin Xie; Jingwei Liu; Xichen Jin; Xiangbiao Zeng; Ziqian Shen; Yanhe Liu; Kang Li; Liping Liu (Journal of Oceanology and Limnology, 2026)

Study on the removal and ecological risk of microplastics in road runoff by collapsible loess bioretention facilities - Wang Xiaojuan; Yan Yaping; Song Xichen; Zhou Jianqiang; Liu Xiuyun; Zhang Tingting; Gao Suxia; Li Jiapeng; Liu Jianlin; Cao Lianbao; Li Wei; Wei Bigui (Process Safety and Environmental Protection, 2026)

Preface to the Special Issue on Atmospheric and Oceanic Processes in the Antarctic and Their Climate Effects: 40 Years of CHINARE - Zhaomin Wang; Bingyi Wu; Wen Zhou; Jiping Liu; Anmin Duan; Xianyao Chen; Ruibo Lei; Minghu Ding; Xichen Li; Wenju Cai (Advances in Atmospheric Sciences, 2025)

Regional Perspective of Hadley Circulation and Its Uncertainties among Different Datasets: Biases of ENSO-Related Hadley Circulation in CMIP Models - Wenzhu Wang; Juan Feng; Yadi Li; Yujie Miao; Xichen Li (Advances in Atmospheric Sciences, 2025)

Dynamic Characteristic (Axial Impedances) of a Novel Sandwich Flexible Insert with Fluid - Leipeng Song; Lulu Chang; Feng Li; Xinjian Xiang; Zhiyong Yin; Xichen Hou; Yongping Zheng; Xiaozhou Xu; Yang Li; Zhihua Huang (Journal of Marine Science and Engineering, 2025)
Piping systems can be analogized to the “vascular systems” of vessels, but their transmission characteristics often result in loud noises and large vibrations. The integration of flexible inserts within these piping systems has been shown to isolate and/or mitigate such vibrations and noise. In this work, a novel sandwich flexible insert (NSFI) was presented specifically to reduce the vibrations and noise associated with piping systems on vessels. In contrast to conventional flexible inserts, the NSFI features a distinctive three-layer configuration, comprising elastic inner and outer layers, along with a honeycomb core exhibiting a zero Poisson’s ratio. The dynamic characteristics, specifically axial impedance, of the fluid-filled NSFI are examined utilizing a fluid–structure interaction (FSI) four-equation model. The validity of the theoretical predictions is corroborated through finite element analysis, experimental results, and comparisons with existing literature. Furthermore, the study provides a comprehensive evaluation of the effects of geometric and structural parameters on the dynamic characteristics of the NSFI. It is worth noting that axial impedance is significantly affected by these parameters, which suggests that the dynamic characteristics of the NSFI can be customized by parameter adjustments.

Characterization of cyclophilin 23 as a novel factor for development and pathogenicity of Cryptosporidium parvum - Mengfei Xu; Xichen Zhang; Qile Yu; Qi Zhao; Jianhua Li; Pengtao Gong; Xiaocen Wang; Xin Li; Xu Zhang; Nan Zhang (Veterinary Parasitology, 2025)

Reassessing the ENSO-related Hadley circulation contraction from a regional perspective - Yujie Miao; Tao Lian; Juan Feng; Yadi Li; Wenzhu Wang; Yurong Hou; Xichen Li (Atmospheric Research, 2025)

Impact of Indian Ocean sea surface temperature anomalies on winter wheat yields in China - Hui Ren; Xiufen Li; Pengkun Liu; Yi Zhou; Tianyi Zhang; Xichen Li (Theoretical and Applied Climatology, 2025)

Remediation of Heavy Metal Contaminated Soil by Functional Pellets of Charcoal Organic Fertilizer: Rhizosphere and Non-Rhizosphere Soil Microorganisms - Fanghong Li; Xichen Zhao; Renli Qi; Liuqin He; Dan Wan; Jiachao Zhang; Xiaobing Zhang; Ying Wang; Genyi Wu; Hongli Huang; Lin Luo; Lihua Zhang (Water, Air, & Soil Pollution, 2025)

Mixing mechanisms of hydrogen-blended natural gas in subsea pipelines: Effects of injection angles - Fenghui Han; Xichen Mu; Ying Wei; Wenhua Li; Zhe Wang (Ocean Engineering, 2025)

Tropical Indian Ocean warming drives an increase in bering sea ice concentration - Yonghao Wang; Xi Liang; Haibo Bi; Yurong Hou; Xichen Li (Climate Dynamics, 2025)

Remote effect of tropical South Atlantic variability on the Pacific–Japan pattern - Wenwen Yang; Xichen Li; Lin Wang; Yurong Hou; Yonghao Wang; Yujie Miao; Weihan Ma (Climate Dynamics, 2025)

Responses of water–carbon coupling to seasonal drought in different land use types in Northwest China - Xin Yuan; Liang Jiao; Ruhong Xue; Xichen Che; Jingjing Wu; Qian Li; Xuge Wang; Zhengdong Guo (Hydrological Sciences Journal, 2025)

An RPA-CRISPR/Cas12a-assisted method for nucleic acid detection of Haemonchus contortus in sheep - Yutong Cao; Qiankun Yang; Yanbing Guo; Xiaocen Wang; Xin Li; Nan Zhang; Wenxue Lu; Jianhua Li; Xichen Zhang; Lili Cao; Pengtao Gong (Veterinary Parasitology, 2025)

Inhibition of Neospora caninum activity by niclosamide: Evidence from in vitro and in vivo studies - Feixue Liu; Xin Li; Liuzhenxiu Yan; Xu Zhang; Jin Sun; Haitao Su; Lu Li; Sining Chen; Lanbi Gao; Pengtao Gong; Nan Zhang; Xichen Zhang; et al. (Veterinary Parasitology, 2025)

The instabilities of the Antarctic slope current in an idealized model - Chengyan Liu; Zhaomin Wang; Xi Liang; Xiang Li; Xianxian Han; Wenjin Sun; Yang Wu; Xichen Li; Chen Cheng (Journal of Marine Systems, 2025)

Assessments of Data-Driven Deep Learning Models on One-Month Predictions of Pan-Arctic Sea Ice Thickness - Chentao Song; Jiang Zhu; Xichen Li (Advances in Atmospheric Sciences, 2024)

The linkage between wintertime sea ice drift and atmospheric circulation in an Arctic ice-ocean coupled simulation - Xi Liang; Haibo Bi; Chengyan Liu; Xichen Li; Dakui Wang; Fu Zhao; Zhongxiang Tian; Ming Li; Na Liu (Ocean Modelling, 2024)

Pyrolysis and combustion characteristics of typical sealing materials for exterior building windows - Yaqing Li; Jie Yang; S. Zeinali Heris; Yutao Zhang; Xichen Zhang; Jiannan Chen (Fuel, 2024)

Resonance between projected Tibetan Plateau surface darkening and Arctic climate change - Shuchang Tang; Shilong Piao; David M. Holland; Fei Kan; Tao Wang; Tandong Yao; Xichen Li (Science Bulletin, 2024)

The technology of suppression containment for the SMR in floating nuclear power plants against hydrogen risk - Jialei Chen; Xuefeng Lyu; Fang Liu; Yu Yu; Fenglei Niu; Qingyao Song; Xichen Li (Annals of Nuclear Energy, 2024)

Study on the water-carbon coupling coordination function on the eastern edge of the Qinghai-Tibet plateau - Xin Yuan; Liang Jiao; Xichen Che; Jingjing Wu; Xuli Zhu; Qian Li (Ecological Modelling, 2024)

Uncertainties of ENSO-related Regional Hadley Circulation Anomalies within Eight Reanalysis Datasets - Yadi Li; Xichen Li; Juan Feng; Yi Zhou; Wenzhu Wang; Yurong Hou (Advances in Atmospheric Sciences, 2024)

A broadscale shift in antarctic temperature trends - Meijiao Xin; Xichen Li; Sharon E. Stammerjohn; Wenju Cai; Jiang Zhu; John Turner; Kyle R. Clem; Chentao Song; Wenzhu Wang; Yurong Hou (Climate Dynamics, 2023)

China’s Recent Progresses in Polar Climate Change and Its Interactions with the Global Climate System - Xichen Li; Xianyao Chen; Bingyi Wu; Xiao Cheng; Minghu Ding; Ruibo Lei; Di Qi; Qizhen Sun; Xiaoyu Wang; Wenli Zhong; Lei Zheng; Meijiao Xin; et al. (Advances in Atmospheric Sciences, 2023)

Profiles of muscular amino acids, fatty acids, and metabolites in Shaziling pigs of different ages and relation to meat quality - Yehui Duan; Changbing Zheng; Jie Zheng; Lu Ma; Xinran Ma; Yinzhao Zhong; Xichen Zhao; Fengna Li; Qiuping Guo; Yulong Yin (Science China Life Sciences, 2023)

Southern Ocean warming and its climatic impacts - Wenju Cai; Libao Gao; Yiyong Luo; Xichen Li; Xiaotong Zheng; Xuebin Zhang; Xuhua Cheng; Fan Jia; Ariaan Purich; Agus Santoso; Yan Du; David M. Holland; et al. (Science Bulletin, 2023)

Rice yield benefits from historical climate warming to be negated by extreme heat in Northeast China - Xin Dong; Tianyi Zhang; Xiaoguang Yang; Tao Li; Xichen Li (International Journal of Biometeorology, 2023)

The potential mechanisms of the dominant timescale of AMOC multidecadal variability in CMIP6/CMIP5 preindustrial simulations - Xiaofan Ma; Gang Huang; Xichen Li; Shouwei Li (Climate Dynamics, 2023)

Impacts of the long-term atmospheric trend on the seasonality of Antarctic sea ice - Fu Zhao; Xi Liang; Zhongxiang Tian; Chengyan Liu; Xichen Li; Yun Yang; Ming Li; Na Liu (Climate Dynamics, 2023)

Air-Backed Aluminum Shells Subjected to Underwater Penetration: Torpedo Interception Simulations - Chucai Peng; Chufan Ding; Bin Chen; Xichen Sun; Weibing Li; Taotao Qin; Jun Feng (Journal of Marine Science and Engineering, 2023)
Underwater torpedoes have become a serious threat to ocean liners and warships, and the interception against attacking torpedoes is always the hotspot in marine engineering. To simulate the underwater torpedo interception by a high velocity projectile, this work numerically deals with the process of projectile water entry and sequent penetration into underwater aluminum shells, whereby conical and ogival nose projectiles are comparatively studied. With the arbitrary Lagrange–Euler (ALE) algorithm adopted to describe fluid medium, the projectile water entry model is developed and validated against the test data. Similarly, the penetration model validation is made by modeling a tungsten ball perforation on an aluminum plate. Covered by water fluid, the air-backed aluminum shell is utilized to simulate an underwater torpedo subjected to projectile impact. The numerical predictions of underwater penetration reveal that ogival nose projectiles have a superior performance in underwater motion and perforation while conical nose counterparts deteriorate the shell targets more severely. For 20 cm, 40 cm and 60 cm underwater depth scenarios, a numerical prediction suggests that the energy consumed by water is proportional to the water depth, meanwhile aluminum shell perforation absorbs almost the identical projectile kinetic energy. Such findings may shed some light on the nose shape optimization design of high velocity projectile intercepting underwater torpedoes.

New record of explosive warmings in East Antarctica - Sai Wang; Minghu Ding; Ge Liu; Shoudong Zhao; Wenqian Zhang; Xichen Li; Wen Chen; Cunde Xiao; Dahe Qin (Science Bulletin, 2023)

Effects of Zinc Lactate Supplementation on Growth Performance, Intestinal Morphology, Serum Parameters, and Hepatic Metallothionein of Chinese Yellow-Feathered Broilers - Lina Long; Xichen Zhao; Haojie Li; Xia Yan; Huihua Zhang (Biological Trace Element Research, 2022)
In poultry, organic zinc compounds have higher bioavailability than inorganic zinc sources. However, as an organic zinc source, the application of zinc lactate (ZL) on Chinese yellow-feathered broilers has been rarely reported. Hence, the present study aimed to investigate the effects of ZL supplementation on growth performance, small intestinal morphology, serum biochemical parameters, immune organ index, as well as hepatic metallothionein of Chinese yellow-feathered broilers. A total of 2100 broilers (19 days old) were randomly assigned to 5 treatment groups, including the control (fed basal diet), ZL40 (basal diet plus 40 mg/kg ZL), ZL60 (basal diet plus 60 mg/kg ZL), ZL80 (basal diet plus 80 mg/kg ZL), and ZS80 (basal diet plus 80 mg/kg ZS. Each treatment group had 6 replicates with 70 chickens per replicate. Compared to the control group, the ZL40 and the ZS80 groups had a lower feed to gain ratio ( P < 0.05), ZL40 group had higher duodenum and ileum villus heights ( P < 0.05), and ZS80 and ZL80 groups had a lower ratio of villus height to crypt depth in the jejunum ( P < 0.01). In addition, the ZL60 group had a higher concentration of total protein ( P < 0.05) and activity of glutathione peroxidase (GSH-Px) ( P < 0.01) compared with the ZS80 and the control groups. Interestingly, the ZL40, ZL60, and ZL80 groups all had higher levels of hepatic metallothionein than the other groups ( P < 0.01). In conclusion, zinc lactate had a higher bioavailability and could be used as an alternative to zinc sulfate.

A Newly Discovered Dense Granule Protein 3 in Neospora caninum - Panpan Zhao; Jingquan Dong; Lili Cao; Jianhua Li; Xichen Zhang; Xin Li; Xiaocen Wang; Babatunde Kazeem Bello; Nan Zhang; Pengtao Gong (Acta Parasitologica, 2021)

Enhanced antitumor activity of inulin-capped Se nanoparticles synthesized using Jerusalem artichoke tubers - Taili Shao; Wei Liu; Pingchuan Yuan; Xichen Li; Honggang Xu; Chunyan Liu; Kaoshan Chen; Lihua Li; Jun Han; Guodong Wang (Glycoconjugate Journal, 2021)

Evolving AMOC multidecadal variability under different CO2 forcings - Xiaofan Ma; Wei Liu; Natalie J. Burls; Changlin Chen; Jun Cheng; Gang Huang; Xichen Li (Climate Dynamics, 2021)

The importance of inter‐basin atmospheric teleconnection in the SST footprint of Atlantic multidecadal oscillation over western Pacific - Cheng Sun; Yusen Liu; Jiaqing Xue; Fred Kucharski; Jianping Li; Xichen Li (Climate Dynamics, 2021)

Identification of mecciRNAs and their roles in the mitochondrial entry of proteins - Xu Liu; Xiaolin Wang; Jingxin Li; Shanshan Hu; Yuqi Deng; Hao Yin; Xichen Bao; Qiangfeng Cliff Zhang; Geng Wang; Baolong Wang; Qinghua Shi; Ge Shan (Science China Life Sciences, 2020)

Specific Relationship between the Surface Air Temperature and the Area of the Terra Nova Bay Polynya, Antarctica - Yifan Ding; Xiao Cheng; Xichen Li; Mohammed Shokr; Jiawei Yuan; Qinghua Yang; Fengming Hui (Advances in Atmospheric Sciences, 2020)

Atlantic effects on recent decadal trends in global monsoon - Youichi Kamae; Xichen Li; Shang-Ping Xie; Hiroaki Ueda (Climate Dynamics, 2017)

Complete genome sequence and evolution analysis of Eimeria stiedai RNA virus 1, a novel member of the family Totiviridae - Caiyan Xin; Bin Wu; Jianhua Li; Pengtao Gong; Ju Yang; He Li; Xuepeng Cai; Xichen Zhang (Archives of Virology, 2016)

Eimeria tenella: a novel dsRNA virus in E. tenella and its complete genome sequence analysis - Bin Wu; Xichen Zhang; Pengtao Gong; Mingying Li; He Ding; Caiyan Xin; Na Zhao; Jianhua Li (Virus Genes, 2016)

Cytochrome P450 2A13 is an efficient enzyme in metabolic activation of aflatoxin G1 in human bronchial epithelial cells - Zhan Zhang; Xuejiao Yang; Yun Wang; Xichen Wang; Huiyuan Lu; Xiaoming Zhang; Xue Xiao; Shushu Li; Xinru Wang; Shou-Lin Wang (Archives of Toxicology, 2013)

Protective effect of gossypol on lipopolysaccharide-induced acute lung injury in mice - Zhicheng Liu; Zhengtao Yang; Yunhe Fu; Fenyang Li; Dejie Liang; Ershun Zhou; Xiaojing Song; Wen Zhang; Xichen Zhang; Yongguo Cao; Naisheng Zhang (Inflammation Research, 2013)

Salidroside attenuates inflammatory responses by suppressing nuclear factor-κB and mitogen activated protein kinases activation in lipopolysaccharide-induced mastitis in mice - Depeng Li; Yunhe Fu; Wen Zhang; Gaoli Su; Bo Liu; Mengyao Guo; Fengyang Li; Dejie Liang; Zhicheng Liu; Xichen Zhang; Yongguo Cao; Naisheng Zhang; et al. (Inflammation Research, 2013)

The impact of mean dynamic topography on a sea-level anomaly assimilation in the South China Sea based on an eddy-resolving model - Dazhi Xu; Jiang Zhu; Yiquan Qi; Xichen Li; Youfang Yan (Acta Oceanologica Sinica, 2012)